Reconceptualization of the Recognition of the Unity of Customary Law Communities in Indonesian Legislation - Suriadiata, Irpan (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This study investigates the recognition of customary law communities in Indonesian legislation, with the objective of redefining the notion to better align with the evolving dynamics of customary law communities and the requirements of contemporary legal systems. This study employs a normative technique, which involves a systematic analysis of positive legal provisions, as well as an empirical sociological approach that encompasses the identification of unwritten laws and research on the efficacy of the law. The data utilized comprises primary, secondary, and tertiary legal sources, obtained by traditional documentation research methods and information technology. The study findings suggest that current legislation has not adequately addressed the presence and rights of customary law communities. Hence, it is imperative to develop a more inclusive and cohesive reinterpretation of the notion of recognition that not only acknowledges the presence of customary law communities, but also ensures the effective safeguarding and enhancement of their rights. This study aims to enhance the development of legal policies that are more equitable and more aligned with the requirements of customary law communities in Indonesia.